Amyrins from Protium heptaphyllum Reduce High-Fat Diet-Induced Obesity in Mice via Modulation of Enzymatic, Hormonal And Inflammatory Responses - Carvalho, Karine Maria Martins Bezerra; de Melo, Tiago Sousa; de Melo, Karina Moura; Quinderé, Ana Luiza Gomes; de Oliveira, Francisca Tuelly Bandeira; Viana, Ana Flávia Seraine Custódio; Nunes, Paulo Iury Gomes; Quetz, Josiane da Silva; Viana, Daniel de Araújo; da Silva, Armenio André de Carvalho Almeida; Havt, Alexandre; Fonseca, Said Gonçalves da Cruz; Chaves, Mariana Helena; Rao, Vietla Satyanarayana; Santos, Flávia Almeida (Planta Medica, 2017)
Obesity remains a global problem. In search of phytochemicals that have antiobesity potential, this study evaluated α,β-amyrin, a triterpenoid mixture from Protium heptaphyllum, on high-fat diet-induced obesity in mice. Groups of mice (n = 8) were fed a normal diet or a high-fat diet, and were orally treated or not treated with either α,β-amyrin (10 or 20 mg/kg) or sibutramine (10 mg/kg) for 15 weeks. Variables measured at termination were body weight, visceral fat accumulation, adipocyte surface area, peroxisome proliferator-activated receptor gamma, and lipoprotein lipase expressions in adipose tissue, the levels of plasma glucose and insulin, the satiety hormones ghrelin and leptin, the digestive enzymes amylase and lipase, and the inflammatory mediators TNF-α, interleukin-6, and MCP-1. Results showed that α,β-amyrin treatment resulted in lower high-fat diet-induced increases in body weight, visceral fat content, adipocyte surface area, peroxisome proliferator-activated receptor gamma, and lipoprotein lipase expressions, and blood glucose and insulin levels. Additionally, the markedly elevated leptin and decreased ghrelin levels seen in the high-fat diet-fed control mice were significantly modulated by α,β-amyrin treatment. Furthermore, α,β-amyrin decreased serum TNF-α and MCP-1. These results suggest that α,β-amyrin could be beneficial in reducing high-fat diet-induced obesity and associated disorders via modulation of enzymatic, hormonal, and inflammatory responses.
Keywords: Protium heptaphyllum; Burseraceae; α,β-amyrin; pentacyclic triterpene; high-fat diet; antiobesity